“MAKING IT WORK” – PRACTICE EXAMPLES OF PREPARATION AND EMBEDDING PEER-TO-PEER LECTURE FILMS IN SUCCESSFUL INVERTED CLASSROOM SCENARIOS - Pfennig, Anja (PEOPLE: International Journal of Social Sciences, 2019)
Embedding lecture videos in “inverted classroom” teaching scenarios has been proven successful in teaching material science to first year mechanical and automotive engineering students at HTW Berlin. These videos covering difficult scientific background knowledge such as precipitation hardening, duplex steels, materials testing and heat treatment as well as lattice defects, composits and corrosion were initiated from students needs and learning experiments. Therefore a student project was defined for production of lecture films each semester supervised closely by the lecturer and film expert. This peer-to-peer approach is essential because the students immediately include their own learning experience and strategy into the set of films and therefore directly implement their perspective and scientific needs within the digital teaching material. Along with recording of lectures the lecture films provide for excellent self-study material suitable for inverted classroom scenarios. Because students already use videos as learning source they appreciated the possibility work independently, appeared active, well prepared and motivated given the self-study period was facilitated well and the contents were in alignment with the overall learning outcome of the course. Also, the quality of the lecture videos influences the learning behavior. Here, sequences of the teaching method are qualitatively evaluated by practice examples encouraging lecturers to get started with digital learning material and the inverted classroom teaching method.